Pain patterns in italian patients with osteoarthritis: preliminary results of the MI.D.A. Study (Misurazione del Dolore nell'Artrosi) - L. Punzi; S. Adami; S. Bombardieri; F.P. Cantatore; V. Modena; W. Grassi; P. Sarzi Puttini; F. Trotta; I. Olivieri; F. Salaffi; M.A. Cimmino; G. Lapadula; et al. (PAGEPress Publications, 2011)
Objectives. To evaluate the characteristics of pain in a cohort of Italian patients with osteoarthritis (OA) of the hip and knee. Methods. The 657 general practitioners participating in the study were asked to enroll 10 consecutive patients with OA diagnosed according to the American College of Rheumatology (ACR) clinical criteria. A questionnaire evaluating demographic data, clinical characteristics of OA, including the "Questionario Semantico Reumatologico" (QSR) pain questionnaire, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the Lequesne indices, and information on previous diagnostic and therapeutic interventions was administered. Results. A total of 4,109 patients were enrolled. Of them, 2356 were affected by knee OA and 1817 by hip OA. There were 2863 (69.7%) women and 1246 (30.3%) men. Median age was 68.2 years (range 50-103 years). Of the 4109 enrolled subjects, 3128 (76.1%) reported one or more medical comorbidities, mostly cardiovascular (52.7%), endocrinological (14.7%), gastrointestinal (13.4%), and respiratory (11.2%) disorders. The median pain visual analogue scale (VAS) score was 58.1±22.6 mm, higher in women (60.2±22.3 mm) than in men ( 53.3±22.6mm) (p<0.00001). OA pain was also higher in patients from Southern Italy (p<0.00001). NSAIDs were administered to nearly 70% of patients, COX-2 inhibitors to 55%, disease-modifying anti OA drugs to 19% and analgesics to 28.2%. Differences in drugs utilization were associated with OA localization and patient's geographical origin. Results of the WOMAC index were similar throughout groups. Responses to the QSR pain questionnaire showed differences, which are related to OA localization and geographical origin of the patients. Conclusions. The MI.D.A. study can help to better understand the patterns of pain in osteoarthritis and the associated treatment.